Angola-Zaïre sur Seine. Identités postcoloniales et hybridités urbaines dans le roman policier Agence Black Bafoussa de Achille F. Ngoye - Fabrice Schurmans (e-cadernos ces, 2019)
Agence Black Bafoussa (1996) offers a fictional representation of a poorly known social milieu, that of communities from sub-Saharan Africa living in Paris. Though the protagonists’ country of origin is imaginary, the reader easily identifies many allusions to Zaire and the end of the Mobutu regime. Therefore, in the first part, this essay situates the novel in the political context of a Zaire in crisis. Then, it examines the literary context in order to argue that the novel simultaneously integrates the categories of the French-speaking African novel and of the crime novel. This perspective opens up for an in-depth textual analysis which identifies the main characteristic of the work: the transformation of Paris into a postcolonial space marked by hybrid cultures with African origins. This essay pays particular attention to the character of the detective, Laurent Cardoso, an Angolan white, because he illustrates the complexity of the identities present in the novel.